Financial Literacy and Financial Management: Mediating Effects of Financial Technology - Anugraini, Mardiyah; Jannah, Sifa Imroatun; Khusnah, Hidayatul; Anshori, Mohamad Yusak; Wijayanti, Destin Rafika (Universitas Nahdlatul Ulama Surabaya, 2023)
Technology and communication are currently developing so rapidly that they are changing human life. Especially in the financial sector, with the aim of providing convenience to the community and increasing productivity and effectiveness. Despite the convenience provided by financial technology, there are quite a few people who still don't understand financial literacy, how to build good financial management skills and a general understanding of financial technology. This research aims to find empirical evidence and analyze the mediating influence of the use of financial technology on the influence of financial literacy on financial management. The sampling method used was the purposive sampling method and the total sample was 85 respondents who were the research objects. The data analysis method is quantitative descriptive analysis using primary data and hypothesis testing using WarpPLS 8.0 software. The test results show that financial literacy has a positive and significant effect on financial management. Financial literacy has a positive and significant effect on financial technology. While financial technology has a positive and significant effect on financial management, financial technology can mediate financial literacy on financial management